2019
DOI: 10.30881/npcij.00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of applying a clinical pathway for patients with Congestive Heart Failure on their health status outcomes

Abstract: Over time, heart failure (HF) turns into a typical cardiovascular condition whose occurrence and predominance are increasing. Being a typical cause for urgent hospital admission, it is a noteworthy cause for morbidity and mortality for patients with CHF. In Egypt around 1.5 million individuals have CHF. A multidisciplinary approach appears the most ideal approach to manage patients with HF since it has been appeared to enhance clinical outcome and particularly to diminish the rate of readmission related to acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The implementation of the clinical pathway guidelines, which comprised care elements linked to a healthy low salt and fat diet, fluid reduction, constant weight monitoring, as well as diuretics medication dose at the right time, may have helped the Clinical Pathway group improve. This result was in line with that of Mohamed et al (2016), who found that while the majority of the study group showed no signs of edema, the control group's two-thirds needed 10-12 seconds to recover from a 6mm-deep pit.…”
Section: Discussionsupporting
confidence: 90%
“…The implementation of the clinical pathway guidelines, which comprised care elements linked to a healthy low salt and fat diet, fluid reduction, constant weight monitoring, as well as diuretics medication dose at the right time, may have helped the Clinical Pathway group improve. This result was in line with that of Mohamed et al (2016), who found that while the majority of the study group showed no signs of edema, the control group's two-thirds needed 10-12 seconds to recover from a 6mm-deep pit.…”
Section: Discussionsupporting
confidence: 90%
“…Various CPs, ranging from acute surgical procedures to chronic diseases, have been introduced in hospital settings (Campbell et al, 1998 ; Chawla et al, 2016 ; Dy et al, 2005 ; Hindle & Yazbeck, 2005 ; Mohamed et al, 2019 ; Vanhaecht et al, 2006 ; Vanhaecht et al, 2009 ). These CPs are intended to reduce patients' length of stay, readmissions, and costs, and improve clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%